Highly efficient LaCr0.75M0.25O3+δ (M= Ti, Mn, Fe, Co and Cu) nanostructured electrodes for Solid Oxide Fuel Cells - Zamudio-García, Javier; Porras-Vázquez, José Manuel; Losilla, Enrique R.; Marrero-López, David (My University, 2019)
Nanostructured composites electrodes based on lanthanum chromites has been prepared using Spray-pyrolysis precursor method achieving better Rp as SOFC electrodes. The performance in real SOFC is still in progress.
Solid Oxide Fuel Cells (SOFCs) are considered as one of the most efficient electrochemical devices for power generation. One of the most effective strategies to enhance the electrode performance is the infiltration into a porous electrolyte to increase the triple-phase-boundary (TPB) leading to highly efficient devices. In this way, Spray-pyrolysis deposition is an easy and scalable method that has been used previously to obtain nanocrystalline electrodes, with a considerable improvement in comparation with conventional electrodes.1 In this work, a new doping strategy in lanthanum chromite-based materials has been carry out to obtain potential anodes/cathodes for SOFCs. LaCrO3 and LaCr0.75M0.25O3 (M= Ti, Mn, Fe, Co and Cu) materials were obtained using Spray-Pyrolysis and Freeze-dry precursor method (FD) simultaneously for further comparation. YSZ pellets were made from commercial powders (Tosoh) pressed into disk and sintered at 1400 ºC for 4h. Afterwards, a Ce0.9Gd0.1O1.95 a porous thin layer was printed and sintered at 1200 ºC for 1h. The electrolyte was sprayed with a precursor solution contain the corresponding nitrates in Milli-Q water with a concentration of 0.025 M. The optimum temperature deposition, time and flow rate was 325 ºC, 1h and 20 mL/min respectively. After the deposition, the samples were calcined at 800 ºC for 1h to achieve crystallization. Simultaneously, the materials were synthesized by Freeze-dry precursor method using the corresponding nitrates in distilled water and adding 1:1 molar ratio of etilendiaminetetraacetic acid (EDTA) as a complexing agent. The resulting solution were frozen in liquid nitrogen, followed by dehydration by vacuum sublimation for 2 days. The dry powers were calcined at 300 ºC for 1h and 800 ºC 1h to eliminate carbonaceous species and phase formation. XRD patterns shows that single phase is achieved for LaCr0.75(Ti, Mn, Fe)0.25O3 and LaCr0.75Cu0.25O3 at 800 and 900 ºC, respectively. The electrode polarization resistance (Rp) was determined by impedance spectroscopy obtaining ASR values as low as 0.1 and 0.35 Ω•cm-1 at 750 ºC in air and 5%-H2/Ar for LaCr0.75Mn0.25O3(LCM), respectively being these values almost one magnitude order better in comparation with related materials.2
Keywords: Electrodos; Pilas de combustible; Electroquímica; SOFC; Nanostructured anodes; Spray pyrolisis; Lanthanum chromites